EFEKTIVITAS MEDIA INTERAKTIF SMART TV DALAM MENINGKATKAN HASIL BELAJAR SISWA SDN PANGERAN 1 - Mutmainah, Siti; Nazwa Azkia Ramadhani; Siti Jamilah; Ibrena Nalsal Angelika Sembiring; Ahmad Suriansyah; Wahdah Refia Rafianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Technology-based learning is essential in the digital era to create interactive, engaging, and meaningful learning experiences for elementary school students. However, many schools have not fully utilized digital media, resulting in monotonous teacher-centered instruction. This study aims to analyze the effectiveness of interactive Smart TV media in improving student learning outcomes at SDN Pangeran 1. A descriptive qualitative method was employed, with data collected through observations, interviews, and documentation involving teachers and students who used Smart TV during learning activities. Data were analyzed through reduction, display, and conclusion drawing. The findings indicate that Smart TV effectively enhances students’ conceptual understanding, motivation, and participation through visual-audio presentations, educational videos, and interactive activities using applications such as YouTube, Quizizz, and Ruang Siswa. Teachers also benefit from real-time monitoring through digital assessments. Challenges include unstable internet connectivity and varying student readiness in operating devices, which can be addressed through guidance and offline content preparation. Overall, interactive Smart TV media provides significant contributions to improving learning quality and is recommended for sustainable integration into elementary learning practices.